VEGFR-3 signaling in macrophages: friend or foe in disease? - Kannan, Saranya; Rutkowski, Joseph M. (Frontiers in Immunology, 2024)
Lymphatic vessels have been increasingly appreciated in the context of immunology not only as passive conduits for immune and cancer cell transport, but also as key in local tissue immunomodulation. Targeting lymphatic vessel growth and potential immune regulation often takes advantage of vascular endothelial growth factor receptor-3 (VEGFR-3) signaling to manipulate lymphatic biology. A receptor tyrosine kinase, VEGFR-3 is highly expressed on lymphatic endothelial cells and its signaling is key in lymphatic growth, development, and survival and, as a result, often considered to be “lymphatic-specific” in adults. A subset of immune cells, notably of the monocyte-derived lineage, have been identified to express VEGFR-3 in tissues from the lung to the gut and in conditions as varied as cancer and chronic kidney disease. These VEGFR-3+ macrophages are highly chemotactic toward the VEGFR-3 ligands VEGF-C and VEGF-D. VEGFR-3 signaling has also been implicated in dictating the plasticity of these cells from pro-inflammatory to anti-inflammatory phenotypes. Conversely, expression may potentially be transient during monocyte differentiation with unknown effects. Macrophages play critically important and varied roles in the onset and resolution of inflammation, tissue remodeling, and vasculogenesis: targeting lymphatic vessel growth and immunomodulation by manipulating VEGFR-3 signaling may thus impact macrophage biology and their impact on disease pathogenesis. This mini review highlights the studies and pathologies in which VEGFR-3+ macrophages have been specifically identified, the activity and polarization changes that macrophage VEGFR-3 signaling may elicit, and affords some conclusions as to the importance of macrophage VEGFR-3 signaling in disease.